A Throughfall Collection Method Using Mixed Bed Ion Exchange Resin Columns - Mark E. Fenn; Mark A. Poth; Michael J. Arbaugh (The Scientific World Journal)
Measurement of ionic deposition in throughfall is a widely used method for measuring deposition inputs to the forest floor. Many studies have been published, providing a large database of throughfall deposition inputs to forests. However, throughfall collection and analysis is labor intensive and expensive because of the large number of replicate collectors needed and because sample collection and chemical analyses are required on a stochastic precipitation event-based schedule. Therefore we developed and tested a throughfall collector system using a mixed bed ion exchange resin column. We anticipate that this method will typically require only one to three samplings per year. With this method, bulk deposition and bulk throughfall are collected by a funnel or snow tube and ions are retained as the solution percolates through the resin column. Ions retained by the resin are then extracted in the same column with 2N KCl and analyzed for nitrate and ammonium. Deposition values in throughfall from conventional throughfall solution collectors and colocated ion exchange samplers were not significantly different during consecutive 3- and 4-month exposure periods at a high (Camp Paivika; >35 kg N ha-1 year-1) and a low deposition (Barton Flats; 5–9 kg N ha-1 year-1) site in the San Bernardino Mountains in southern California. N deposition in throughfall under mature pine trees at Camp Paivika after 7 months of exposure was extremely high (87 and 92 kg ha-1 based on the two collector types) compared to Barton Flats (11 and 13 kg ha-1). A large proportion of the N deposited in throughfall at Camp Paivika occurred as fog drip, demonstrating the importance of fog deposition as an input source of N at this site. By comparison, bulk deposition rates in open areas were 5.1 and 5.4 kg ha-1 at Camp Paivika based on the two collector types, and 1.9 and 3.0 kg ha-1 at Barton Flats.